Penerapan Metode Usability Testing dan System Usability Scale untuk Mengevaluasi Website Akademik - Nabila Putri; Febi Nur Salisah; Muhammad Luthfi Hamzah; Tengku Khairil Ahsyar; Arif Marsal (STMIK Budi Darma, 2022)
A web-based academic information system, developed to address the demands of organizations wishing to computerize their educational offerings to improve efficiency, service excellence, competitiveness and the quality of their workforce. The Syarif Kasim Riau Islamic University Animal Husbandry Study Program is one of the universities that has an academic website. This website was launched in 2013 and last updated in 2017, but its quality has never been assessed. This study aims to assess website usability using the System Usability Scale (SUS) test on the Uin Suska Riau Animal Husbandry Research Program website. In this study, usability testing is done by giving tasks to users to complete, and SUS is used to measure user satisfaction with academic websites. Respondents were taken using a random sampling technique with a total of 85 respondents obtained from the slovin formula. In the ranking of adjectives including ok on the class F scale and including unacceptable in the acceptance range category, namely unacceptable websites, the final result is 50.03 according to SUS calculations. The results of this study include 5 recommendations for improvement solutions as a reference for future website development.